River Sediment Transport And Coastal Erosion in The Southeastern Black Sea Rivers - Berkun, Mehmet; Aras, Egemen (Veda, Slovak Acad Sciences, Dubravska Cesta 9, 842 34 Brastislava, Slovakia, 2012)
In the Southeastern Black Sea Region, rivers are dammed for hydroelectric power and irrigation. The natural course of fluvial alluvium transport is almost completely altered because of planned and constructed dams and coastal protection measures. Decreasing volume of sediment carried to the sea cause intensification of the shore erosion. The Black Sea Rivers and coastal areas of Turkey and Georgia are under heavy anthropogenic pressure because of the bed material extraction and coastal erosion rate. In this study, environmental effects of dams and related effects of sediment transport on coastal erosion in the Eastern Black Sea region are discussed.
Keywords: Black Sea; Coruh River; Sediment Load; Dams; Coastal Erosion; Karadeniz; Çoruh Nehri; Tortu Yükü; Barajlar; Kıyı Erozyonu